Monitoring of water level at the Wiesengrundbach in Saxony in Germany from 2021-2023 - Manuel Wewer (PANGAEA, 2023)
Measurements of the microclimate were carried out at the Wiesengrundbach in Saxony in Germany. Some of the measurements were single measurements (wind speed, gust velocity and solar radiation) and some were continuous measurements (water level and water temperature) with periods of several months. The study area covers a 1 kilometer long river section. The data were collected in order to assess the extent to which the water temperature is influenced by the riparian vegetation. The sensors in the water body (water level and water temperature) were installed on the river bed.